AKTUALISASI POLA PENGASUHAN ORANG TUA DALAM PEMBENTUKAN KARAKTER ANAK DI ERA DIGITAL PERSPEKTIF AL-QUR`AN: Pendekatan Tafsir Tematik - Syamsul Ma'arif; Imam Syafi'i (AL ITQAN: Jurnal Studi Al-Qur'an, 2017)
This paper explores how parenting patterns in shaping children's character in the digital era with the perspective of the Qur'an. This is interesting because there is not much literature that discusses this theme in the view of the Qur'an. In today's digital era, almost everyone depends on gadgets, and children are no exception. This era is an era where there is a market for positive and negative things on social media. The spread of hoaxes, hate speech, and radicalism, for example, can be known through social media. This is a challenge that has the potential to affect the character of children who will become the nation's next generation, who should be given proper care so that good character is formed from an early age. Character building from an early age depends much on parenting patterns, because they are the first educators. In addition, the material given to children is also a determining factor in shaping children's character. Talking about parenting patterns in shaping children's character, it turns out that the Al-Qur'an has provided an overview in several letters, which tell how the ideal parenting patterns are carried out by parents towards their children.